RANCANG BANGUN SIMULATOR HUJAN GUNA MENDUKUNG UJI EARLY WARNING SYSTEM UNTUK SIMULASI LONGSORAN PADA LAHAN PERTANIAN - , DINNO HARDIONO; , Dr. Ir. Lilik Sutiarso, M. Eng ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Simulated rainfall was desirable for research such as the study of erosion, infiltration, interception. The simulated rainfall is produced by rainfall simulator. Rainfall simulator is a tool that can be used to study the hydrological parameters such as infiltration and runoff under a controlled use of the rain. Rainfall simulator can be used for research related to the repeatability of natural phenomena, such as research related to natural phenomena such as rain erosion, infiltration and runoff. The aims of this research is designing a rainfall simulator to produce uniform artificial rain and has a certain intensity of rainfall. is The results a rainfall simulator with specifications, Dimensional framework with a length of 255 cm, width of 125 cm and height of 200 cm of water distribution systems using a pump of 20 m total head